1996
DOI: 10.1093/nar/24.8.1453
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in target DNA elements of yeast HAP1 modulate its transcriptional activity without affecting DNA binding

Abstract: The yeast zinc cluster protein HAP1, a member of the GAL4 family, is a transcriptional activator that binds as a homodimer to target DNA sequences. These targets include the upstream activating sequences of the CYC1 and CYC7 genes, which have no obvious sequence similarity. Even though both sites have the same affinity for HAP1, activation differs at these two sites, even when the sequences are placed in an identical promoter context. In addition, mutants of HAP1 that can bind to both sites but are specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…Dimerization is mediated through a parallel coiled-coil element connected to the zinc cluster by a short extended polypeptide. Recognition can also occur with CGG triplets oriented as direct repeats, as in the case of Hap1p (Zhang and Guarante, 1994;Ha et al, 1996), or as inverted palindromes, as shown recently for Leu3p and Pdr3p . Comparisons of the amino acid sequences of the various C 6 zinc cluster proteins as well as of their DNA targets have appeared recently (Schjerling and Homberg, 1996;Todd and Andrianopoulos, 1997).…”
Section: Introductionmentioning
confidence: 66%
“…Dimerization is mediated through a parallel coiled-coil element connected to the zinc cluster by a short extended polypeptide. Recognition can also occur with CGG triplets oriented as direct repeats, as in the case of Hap1p (Zhang and Guarante, 1994;Ha et al, 1996), or as inverted palindromes, as shown recently for Leu3p and Pdr3p . Comparisons of the amino acid sequences of the various C 6 zinc cluster proteins as well as of their DNA targets have appeared recently (Schjerling and Homberg, 1996;Todd and Andrianopoulos, 1997).…”
Section: Introductionmentioning
confidence: 66%
“…Most of these factors are vertebrate nuclear receptors, but there is at least another possible example from yeast, the heme-activated Hap1p factor (64). Our study differs from these in that we have defined genetic correlations between structurally distinct Rap1p-DNA complexes and genes involved in various aspects of transcription regulation.…”
Section: Discussionmentioning
confidence: 95%
“…One possibility is that GAL4 pc mutants simply have an altered conformation that inhibits the activation domain. Examples of this mechanism comes from work on pc mutants of the glucocorticoid receptor (24) and another Zn 2 Cys 6 protein, HAP1 (25), which indicated that appropriate transcription factor-UAS interactions are necessary for optimal transcriptional activation.…”
Section: Discussionmentioning
confidence: 99%